Networks and Social Worlds - Sonia Livingstone; Julian Sefton-Green (Class, 2016)
A key challenge we set ourselves in this book was to understand the relations and interconnections among members of the class. In the introduction and chapter 1, we noted that “networks” and “connectedness” are terms often used in initiatives and visions aiming to improve education, quality of social life, and future life chances, by fostering flexible, extensive, and sometimes unanticipated or creative links among people and across places and spheres of knowledge and activity.¹ In this chapter, we explore how interconnected the members of our class were, in what ways, and what such connections meant to the individuals concerned. In